An axis-specific mitral annuloplasty ring eliminates mitral regurgitation allowing mitral annular motion in an ovine model - Yuanjia Zhu; Annabel M. Imbrie-Moore; Matthew H. Park; Tyler E. Cork; Shin Yajima; Robert J. Wilkerson; Nicholas A. Tran; Mateo Marin-Cuartas; Danielle M. Mullis; Sam W. Baker; Yuko Tada; Tsuyoshi Ueyama; et al. (Communications Medicine)
Abstract Introduction Current mitral annuloplasty rings fail to restrict the anteroposterior distance while allowing dynamic mitral annular changes. We designed and manufactured a mitral annuloplasty ring that demonstrated axis-specific, selective flexibility to meet this clinical need. The objectives were to evaluate ex vivo biomechanics of this ring and to validate the annular dynamics and safety after ring implantation in vivo. Methods Healthy human mitral annuli (n = 3) were tracked, and motions were isolated. Using the imaging data, we designed and manufactured our axis-specific mitral annuloplasty ring. An ex vivo annular dilation model was used to compare hemodynamics and chordal forces after repair using the axis-specific, rigid, and flexible rings in five porcine mitral valves. In vivo, axis-specific (n = 6), rigid (n = 6), or flexible rings (n = 6) were implanted into male Dorset sheep for annular motion analyses. Five additional animals receiving axis-specific rings survived for up to 6 months. Results Here we show the axis-specific, rigid, and flexible rings reduced regurgitation fraction to 4.7 ± 2.7%, 2.4 ± 3.2%, and 17.8 ± 10.0%, respectively. The axis-specific ring demonstrated lower average forces compared to the rigid ring (p = 0.046). Five animals receiving axis-specific rings survived for up to 6 months, with mitral annular motion preserved in vivo. Mature neoendocardial tissue coverage over the device was found to be complete with full endothelialization in all animals. Conclusions The axis-specific mitral annuloplasty ring we designed demonstrates excellent capability to repair mitral regurgitation while facilitating dynamic mitral annular motion. This ring has tremendous potential for clinical translatability, representing a promising surgical solution for mitral regurgitation.